Book of Building As A Source Of Knowledge About The Object. (2017) - Gajzler, Marcin
Abstract: The article presents point of view on the Book of Building object as a potential and valuable source of information and knowledge about the technical condition of the building. As the basis of the research conducted, the significance and the role of the management of the building during its operation were pointed out, focusing on multi-family residential buildings. Their operation is related to the phenomenon of technical consumption, which causes can be found at the design stage. The factors related to the operating phase are significantly influenced by technical factors. These are environmental and utility factors. Maintenance and repair activities are necessary to counteract the wear and tear of the object. Their scheduling currently requires a lot of analysis and experience. In order to support the planning of maintenance activities, a database has been developed, which develops towards the knowledge base and the construction of a management support system. The article presents the structure of the database. The innovative element of this database is the use of text mining techniques to obtain information and represent them. Further research will continue on mining techniques which will be used to build knowledge base.